Genetic dissimilarity between biofortified lettuce genotypes for leaf carotenoid levels - de Sousa, Luciana Alves; Maciel, Gabriel Mascarenhas; Juliatti, Fernando Cezar; Beloti, Igor Forigo; Siquieroli, Ana Carolina Silva; Clemente, Andressa Alves (Comunicata Scientiae, 2020)
Lettuce is the main leafy vegetable, presenting the highest consumption and economic importance in the world. In the recent decades, concerns about vitamin A deficiency have led Brazilian researchers to develop cultivars with higher levels of carotenoids provitamin A. Therefore the experiment aimed to verify the genetic dissimilarity of biofortified lettuce genotypes, investigating the correlation between agronomic characteristics and the potential for use to increase the carotenoid content in future breeding programs. Ninety one genotypes were evaluated, with 86 lettuce strains from hybridization between cultivars Pira 72 versus Uberlândia 10000 (rich in carotenoids) followed by three successive self-fertilizations and 5 commercial cultivars (Grand Rapids; UFU MC BIOFORT1; Pira 72; Uberlândia 10000 and Robusta).During the course of the trial, were evaluated characteristics as chlorophyll content of the leaves, plant diameter, stem diameter and the number of leaves per plant were counted. Genetic diversity was represented by a dendrogram that was obtained using the hierarchical method of UPGMA and the optimization method of Tocher. There is genetic divergence between the lettuce genotypes analyzed, and the carotenoid content character contributed most significantly to the divergence between the evaluated genotypes. The UFU215#12 genotypes; UFU215#14; UFU215#2; UFU 215#1; UFU215#4; UFU199#3 and UFU199#2 have good agronomic characteristics and high levels of carotenoids, being promising to continue the biofortified lettuce breeding program, aiming to obtain new cultivars rich in carotenoids pro vitamin A.